The Experience of Trinitarian Compassion According to St. Francis of Assisi - Krzysztof Juzba (Polonia Sacra)
In this paper I focused on the St. Francis understanding of God`s compassion and mercifulness. Poverello`s idea of the purity and delicacy of God resulted in the description of God`s face as paternal and maternal at the same time. In such a way one and the same God, as portrayed by little poor man of Assisi, approaches each men and every creatures and loves them and compassionates for each His creatures. Trinitarian Compassion according St. Francis means God`s love which creates everything. From the other side all the creatures show God`s love. This love forms the basis of the compassion for man. St. Francis labels such comprehended One God in Three Person: Goodness and Source of all Goodness and Love. Motivated by such an experience of God`s love St. Francis gave away all his belongings to the fellow – creators. St Francis himself contemplated and experienced Divine Mysteries what he described afterwards. He asserted that if somebody loves actually, he is able to give himself to others like Jesus did. True love is the fruit of the act of giving. Francis` mystical experience of God in Three Person lead him to his own inter-trinitarian love. It is impossible to understand the phenomenon of St. Francis compassion to each man and every God’s creations without this Trinitarian dimension.